2019
DOI: 10.13189/ujcm.2019.070101
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality Assessment of Borehole Water in Ogbaru Communities, Anambra State, Nigeria

Abstract: Ogbaru Communities are usually submerged by intense flood during the rainy season, but such flood recedes during the dry season. This natural occurrence makes the quality of the borehole water in the area questionable. The total bacterial, total coliform, faecal coliform and Vibrio cholerae counts of samples from fifteen boreholes in the communities were determined during both seasons using standard analytical methods. The values were 100-270 cfu/100ml;10-42cfu/100ml;0-28 cfu/100ml and 0-13cfu/100ml for total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thus, this support our report that contamination of water could be from the source. Onuorah et al, [21] reported the presence of Klebsiella, Vibrio, Enterobacter and Staphylococcus sp from borehole water in Ogbaru Community, Anambra State, Nigeria while Abdullahi et al, [22] reported the presence of Klebsiella from Staff school, Science Department and female hostel boreholes in Niger State Polytechnic, Zungeru campus. The residents fetch their water from the bore holes; thus, this could be the primary area of contaminant especially since most of these boreholes are sited without proper geological surveys: proximity to toilet, dumpsites, latrines and septic tanks [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this support our report that contamination of water could be from the source. Onuorah et al, [21] reported the presence of Klebsiella, Vibrio, Enterobacter and Staphylococcus sp from borehole water in Ogbaru Community, Anambra State, Nigeria while Abdullahi et al, [22] reported the presence of Klebsiella from Staff school, Science Department and female hostel boreholes in Niger State Polytechnic, Zungeru campus. The residents fetch their water from the bore holes; thus, this could be the primary area of contaminant especially since most of these boreholes are sited without proper geological surveys: proximity to toilet, dumpsites, latrines and septic tanks [23].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of P. mirabilis from river Kuja in Migori county, is inline with the previous studies and therefore drinking water at such a time of sampling could cause diarrhoeal diseases. A study in Nigeria showed that borehole water was a source of V. cholerae, E. coli and Providencia sneebia during rainy and dry seasons 36 . These three bacteria also present in the surface waters of the current study have been reported to cause different forms of diarrhoea hence a health hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the microbial, heavy metal and estrogenic burden of borehole water in Nigeria are also high and of great concern (Adeghe and Emejulu, 2016;Samuel et al, 2019) post SDG implementation. Samuel et al (2019) reported pathogenic bacteria and coliform (including Salmonella Typhi) from borehole samples from Anambra State. Similar outcome was also reported in Rivers State (Obioma et al, Nwinyi et al, 2020 Review of drinking water quality in Nigeria…”
Section: Drinking Water Quality In Nigeria Post-sdg Implementationmentioning
confidence: 99%